Opacification Domain of Serum Opacity Factor Inhibits Beta-Hemolysis and Contributes to Virulence of Streptococcus pyogenes - Luchang Zhu (American Society for Microbiology, 2017)
ABSTRACT Serum opacity factor (SOF) is a cell surface virulence factor made by the human pathogen Streptococcus pyogenes. We found that S. pyogenes strains with naturally occurring truncation mutations in the sof gene have markedly enhanced beta-hemolysis. Moreover, deletion of the sof gene in a SOF-positive parental strain resulted in significantly increased beta-hemolysis. Together, these observations suggest that SOF is an inhibitor of beta-hemolysis. SOF has two major functional domains, including an opacification domain and a fibronectin-binding domain. Using a SOF-positive serotype M89 S. pyogenes parental strain and a panel of isogenic mutant derivative strains, we evaluated the relative contribution of each SOF functional domain to beta-hemolysis inhibition and bacterial virulence. We found that the opacification domain, rather than the fibronectin-binding domain, is essential for SOF-mediated beta-hemolysis inhibition. The opacification domain, but not the fibronectin-binding domain of SOF, also contributed significantly to virulence in mouse models of bacteremia and necrotizing myositis. Inasmuch as the opacification domain of SOF is known to interact avidly with host high-density lipoprotein (HDL), we speculate that SOF-HDL interaction is an important process underlying SOF-mediated beta-hemolysis inhibition and SOF-mediated virulence. IMPORTANCE Streptococcus pyogenes is a major human pathogen causing more than 700 million infections annually. As a successful pathogen, S. pyogenes produces many virulence factors that facilitate colonization, proliferation, dissemination, and tissue damage. Serum opacity factor (SOF), an extracellular protein, is one of the virulence factors made by S. pyogenes. The underlying mechanism of how SOF contributes to virulence is not fully understood. SOF has two major features: (i) it opacifies host serum by interacting with high-density lipoprotein, and (ii) it inhibits beta-hemolysis on blood agar. In this study, we demonstrate that the domain of SOF essential for opacifying serum is also essential for SOF-mediated beta-hemolysis inhibition and SOF-mediated virulence. Our results shed new light on the molecular mechanisms of SOF-host interaction.